دعوى تأثر الإمام الغزالي (ت. 505 هـ.) بالفلسفة والرد عليها - راضي، محمد محسن (جامعة الموصل - كلية العلوم الإسلامية, 2022)
هذا البحث دراسة تتبع فيها الباحث دعوى تأثر الغزالي بالفلسفة، وتبين أنها لا تخرج عن ثلاث أمور، الأولى: دعوى تأثر الغزالي بالفلسفة عندما اطلع على آراءهم، والثانية: دعوى تأثره بالفلسفة بناء على ما نسب إليه من كتب، والثالثة: دعوى تأثره بالفلسفة لاهتمامه بالمنطق والتأليف فيه، ثم أعقبها الباحث بالتحليل والنقد والرد، وكانت نتيجة الدراسة براءة الإمام الغزالي من هذه الدعوى. This article is a study in which the author follows the claim that Al-Ghazali was influenced by philosophy, and it was found that it does not depart from three matters, the first: the claim that Al-Ghazali was influenced by philosophy when he looked at their views, and the second: the claim that he was influenced by philosophy based on what books were attributed to him, and the third: the claim that he was influenced by philosophy because of his interest in logic and the authorship in it, then the author followed it with analysis, criticism and response, and the result of the study was the innocence of Imam Al-Ghazali from this lawsuit.
Keywords: علم الفلسفة -- المذاهب الإسلامية -- المنطق الأرسطي -- الأشعري، محمد الغزالي الطوسي، ت. 505 هـ